The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jpi.12578
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological doses of melatonin impede cognitive decline in tau‐related Alzheimer models, once tauopathy is initiated, by restoring the autophagic flux

Abstract: Alterations in autophagy are increasingly being recognized in the pathogenesis of proteinopathies like Alzheimer's disease (AD). This study was conducted to evaluate whether melatonin treatment could provide beneficial effects in an Alzheimer model related to tauopathy by improving the autophagic flux and, thereby, prevent cognitive decline. The injection of AAV‐hTauP301L viral vectors and treatment/injection with okadaic acid were used to achieve mouse and human ex vivo, and in vivo tau‐related models. Melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 66 publications
3
50
0
Order By: Relevance
“…The Reactive Oxygen Species Assay Kit (Beyotime) was used to measure ROS levels. Embryos in each group (n = [15][16][17][18][19][20] were incubated in serum-free culture medium containing 10 mmol/L dichlorodihydrofluorescein diacetate (DCHF-DA) at 37°C for 20 minutes. The embryos were then washed three times in serum-free culture medium and imaged using a fluorescence microscope equipped with a digital camera (Nikon), followed by analysis using Image-Pro Plus (v6.0; Media Cybernetics).…”
Section: Ros Level Determination In Embryosmentioning
confidence: 99%
See 2 more Smart Citations
“…The Reactive Oxygen Species Assay Kit (Beyotime) was used to measure ROS levels. Embryos in each group (n = [15][16][17][18][19][20] were incubated in serum-free culture medium containing 10 mmol/L dichlorodihydrofluorescein diacetate (DCHF-DA) at 37°C for 20 minutes. The embryos were then washed three times in serum-free culture medium and imaged using a fluorescence microscope equipped with a digital camera (Nikon), followed by analysis using Image-Pro Plus (v6.0; Media Cybernetics).…”
Section: Ros Level Determination In Embryosmentioning
confidence: 99%
“…Apoptosis assays were performed using the DeadEnd Fluorometric TUNEL System (Promega) as previously described. 28 Briefly, embryos (n = [15][16][17][18][19][20] were fixed in 4% paraformaldehyde for 2 hours at RT, permeabilized with 0.5% Triton X-100 for 5 minutes at RT, and incubated in FITCconjugated dUTP and terminal deoxynucleotidyl transferase at 37°C in the dark for 1 hour. The end-labeling reaction was terminated using 2X SSC in the dark at RT for 15 minutes.…”
Section: Apoptosis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, a large amount of immature autophagic vacuoles accumulate in dystrophic neurites in AD brains (45), suggesting that the accumulation of pathogenic proteins such as Ab and tau may be caused by a defective ALP performance (46,47). As NOX4 deficiency reduced the accumulation of pathological oligomeric hyperphosphorylated tau, we sought of interest to evaluate the performance of macroautophagy, a highly characterized proteolysis pathway involved in the clearance of tau (48,49), in the in vivo tauopathy model. Immunofluorescence analysis revealed that the macroautophagy markers p62 ( Figure 3, A and B) and microtubule-associated protein 1 light chain 3 (LC3) ( Figure 3, C and D) were accumulating in the ipsilateral CA1 hippocampal region of NOX4 +/+ AAV-hTau injected mice.…”
Section: Nox4 Deficiency Modulates the Alp In Tauopathymentioning
confidence: 99%
“…neuroinflammation, autophagy dysregulation, etc.) were already established (48). To selectively knockdown neuronal NOX4, we injected AAV serotype 9 particles, which exhibits neuronal tropism for transgene delivery (61), carrying a short hairpin RNA (shRNA) targeting NOX4 (AAV-shNOX4) or a control scramble shRNA (AAV-shSCR) in the right hemisphere´s hippocampus ( Figure 5B).…”
Section: Neuronal Nox4 Knockdown Efficiently Reduces the Accumulationmentioning
confidence: 99%